2018
DOI: 10.1002/jrs.5420
|View full text |Cite
|
Sign up to set email alerts
|

Raman vibrational spectral characteristics and quantitative analysis of H2 up to 400°C and 40 MPa

Abstract: In situ Raman detection is an ideal method to determine the concentration of dissolved H 2 in deep-sea high temperature hydrothermal fluids, but studies on in situ Raman qualitative and quantitative analyses of H 2 that are suitable for detection in high temperature hydrothermal fluids are lacking. In this study, the Raman characteristics of gaseous and dissolved H 2 were researched at 0-400°C and 0-40 MPa in detail, which cover most deep-sea hydrothermal environments. The strong density and temperature depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 76 publications
1
27
0
Order By: Relevance
“…The spectral range (100–4,325 cm −1 ) was split into two regions (100–2,100 and 2,100–4,325 cm −1 ) on the surface of the CCD; therefore, the spectral resolution of the RiP system was approximately 1 cm −1 . [ 21,31 ] Before each deployment, the wavenumber and intensity calibration of the RiP system were processed by neon and halogen lamps.…”
Section: Devices and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The spectral range (100–4,325 cm −1 ) was split into two regions (100–2,100 and 2,100–4,325 cm −1 ) on the surface of the CCD; therefore, the spectral resolution of the RiP system was approximately 1 cm −1 . [ 21,31 ] Before each deployment, the wavenumber and intensity calibration of the RiP system were processed by neon and halogen lamps.…”
Section: Devices and Methodsmentioning
confidence: 99%
“…In addition, the instruments and optical paths used can impact the relationship between spectral intensity and methane concentration. [ 30,31 ] Therefore, a new CH 4 quantitative calibration model suitable for a deep‐sea Raman system needs to be developed to accurately determine the concentration of methane in hydrothermal fluids from in situ Raman spectra.…”
Section: Introductionmentioning
confidence: 99%
“…Lamadrid and colleagues described a relationship between Raman spectral features and fugacity in mixtures of gases . Li et al reported vibrational Raman spectral characteristics and quantitative analysis of H 2 up to 400°C and 40 MPa . Liu et al studied the unravelling of the decomposition products of phosphine under high pressure where it shows superconducting behaviour .…”
Section: High Pressure Temperature Studies Phase Transitions and Gmentioning
confidence: 99%
“…[189] Li et al reported vibrational Raman spectral characteristics and quantitative analysis of H 2 up to 400°C and 40 MPa. [190] Liu et al studied the unravelling of the decomposition products of phosphine under high pressure where it shows superconducting behaviour. [191] Maczka and co-workers described Raman scattering of pressureinduced phase transitions in perovskite-like acetamidninium manganese formate.…”
Section: Metals Carbons and Other Crystalline Materialsmentioning
confidence: 99%
“…Therefore, the characteristic peak assignment, including peaks locating and peak's intensity measuring, is a simple and effective characteristic‐variables‐extracting method . For a longtime study, peaks assignment derives some other feature extraction methods such as half‐spectrum peak width measurement, peak area measurement, peak‐to‐peak line slope measurement, and peak‐to‐peak height ratio measurement . However, compared with mass spectrometry and infrared spectroscopy, Raman spectroscopy has a shorter history.…”
Section: Introductionmentioning
confidence: 99%